Implementation Of The Principle Of Equality Before The Law In The Settlement Of Industrial Relations Disputes In The Industrial Relations Court - Siti Nurhayati (Yayasan Multidimensi Kreatif, 2023)
The State of Indonesia is a State of law. One of the principles of the rule of law is the guarantee of the exercise of the power of an independent judicial institution, free from all interference by extra-judicial powers. The judicial power itself is an independent power, one of which is through the Principle of Objectivity which requires that dispute resolution will be good and acceptable to all parties, if carried out impartially (impartially), objectively, and fairly. The hopes above arise from the existence of the Principle of Equality Before the Law, which is one of the three meanings of the Rule of Law. The principle of Equality Before the Law arises from the modern legal system inspired by the paradigm of Positivism which assumes that the law must be objective and sterile from any influence outside the law. The implementation of the Equality Before The Law Principle in resolving industrial relations disputes at PHI is interesting for further investigation because the parties to the dispute in industrial relations are employers and workers/workers who are socially and economically clearly